Heat Shock Proteins as Danger Signals for Cancer Detection - Seigneuric, Renaud; Mjahed, Hajare; Gobbo, Jessica; Joly, Anne-Laure; Berthenet, Kevin; Shirley, Sarah; Garrido, Carmen (Frontiers in Oncology, 2011)
First discovered in 1962, heat shock proteins (HSPs) are highly studied with about 35,500 publications on the subject to date. HSPs are highly conserved, function as molecular chaperones for a large panel of “client” proteins and have strong cytoprotective properties. Induced by many different stress signals, they promote cell survival in adverse conditions. Therefore, their roles have been investigated in several conditions and pathologies where HSPs accumulate, such as in cancer. Among the diverse mammalian HSPs, some members share several features that may qualify them as cancer biomarkers. This review focuses mainly on 3 inducible HSPs: HSP27, HPS70 and HSP90. Our survey of recent literature highlights some recurring weaknesses in studies of the HSPs, but also identifies findings that indicate that some HSPs have potential as cancer biomarkers for successful clinical applications.